A Critical Investigation of the Bulk Shipping Commodities Trade - Fernandes, Rohit Walter (2010)
Executive Summary The twentieth century has seen an exorbitant increase in sea borne trade that shifted eastwards due to the developing economies like India and China. Most of this trade constituted of the movement of raw materials like coal, iron ore, etc, which were used as inputs for production and manufacturing, thus an increased importance on bulk shipping. Though a large percentage of global sea transport consists bulk shipping, there is insufficient research related studies being conducted on bulk shipping of commodities.